Mapping the Motion Space of Children in Autism Treatment Center of Malang City with TEACCH Approach (Treatment and Education of Autistic and Related Communication Handicapped Children) - Rinawati Pudji Handajani; Rizky H Pramesti (RUAS (Review of Urbanism and Architectural Studies), 2020)
The Autism Treatment Center in Malang City applies structured teaching-learning methods, namely the TEACCH approach (Treatment and Education of Autistic and Related Communication Handicapped Children) with four essential components: physical structure, schedule, work system, and visual structure. The four components are interrelated with each other so that the goal of helping the development of autistic children can be achieved. The physical structure is the first step to encourage the interest of autistic children. An excellent physical arrangement of space can minimize the tantrum effect of autistic children. Thus, this paper aims to research the space for autistic children with the TEACCH approach. This study used behavioral mapping in the form of person-centered mapping, place centered mapping, and physical trace that aims to determine the pattern of activity, furniture layout, and trace activities of autistic children during therapy activities. The results show the motion space mapping of autistic children.